The Encyclopedia of Vaudeville - Slide, Anthony (Book collections on Project MUSE., 2012)
The Encyclopedia of Vaudeville provides a unique record of what was once America's preeminent form of popular entertainment from the late 1800s through the early 1930s. It includes entries not only on the entertainers themselves, but also on those who worked behind the scenes, the theatres, genres, and historical terms. Entries on individual vaudevillians include biographical information, samplings of routines and, often, commentary by the performers. Many former vaudevillians were interviewed for the book, including Milton Berle, Block and Sully, Kitty Doner, Fifi D'Orsay, Nick Lucas, Ken Mur.